The Potential of Cinnamon as Anti-Depressant - Chris Alberto Amin; Afiahana Andatia; Fathia Daffa Putri; Siti Nurhayati Utami; M. Yusuf Wijahaska (HM Publisher, 2021)
Depression is a feeling of loss of interest or pleasure, sadness, feelings of guilt or inferiority, disturbances in sleep or appetite, feelings of tiredness, and poor concentration and the desire to end life. In Indonesia, according to the Indonesian Ministry of Health in 2018, the prevalence of depressive disorders in Indonesia is 6.1%. Based on the 2013 Riskesdas report, the prevalence of suicide in Indonesia is mostly carried out by women, which is around 0.8% compared to men, which has a prevalence of 0.6%. Until now, the first line of depression therapy is the Serotonin Re-Uptake Inhibitor (SSRI) group. Although this drug is effective in improving symptoms of depression, this drug can cause several side effects such as insomnia or drowsiness, weight gain, and sexual dysfunction. Therefore, we need an alternative medicine that can replace conventional medicine which has less side effects. Cinnamon is one of the many plants found in Indonesia which is believed to have the potential to overcome various diseases. Based on previous research, there are many active components contained in cinnamon that have anti-depressant effects. Active components such as Phenol, Cinnamaldehyde, Turmerone, Proanthocyanidin and Linalool as well as Eugenol can provide anti-depressant effects through anti-inflammatory prevention.